ChemInform Abstract: Synthesis of CF3‐Containing 1, 2, 3, 4‐Tetrahydroisoquinoline‐3‐phosphonates via Regioselective Ruthenium‐Catalyzed Co‐Cyclotrimerization of 1, 7‐Azadiynes. Issue 47 (4th November 2013) - Zotova, Maria A.; Vorobyeva, Daria V.; Dixneuf, Pierre H.; Bruneau, Christian; Osipov, Sergey N.
Abstract The synthesis of the title compounds is achieved through N‐propargylation of substrates (I) and (VIII) followed by cyclotrimerization with alkynes.